Strengthening the School Mental Health Ecosystem Through Peer Counseling Service Innovation for High School Students (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
Adolescent mental health is a critical determinant of academic and social success. In some high schools, students face high levels of academic stress and bullying, while the availability of Guidance and Counseling (BK) teachers is severely limited to address the needs of all students. This community service initiative aims to empower selected students as peer counselors to provide initial psychological support and enhance collective awareness among the school community. The implementation method was participatory, involving stages of socialization, intensive training in basic counseling skills such as active listening and empathy, stress management workshops, and the integration of case reporting technology. The results of the activity demonstrated high enthusiasm and a significant improvement in participants’ competence in detecting mental health issues among peers. Students are now able to act as agents of change who provide psychological first aid and understand referral procedures to professionals. This program concludes that empowering peer counselors is an effective and sustainable strategy for addressing gaps in counseling services, reducing stigma, and creating a safe, inclusive educational ecosystem that supports the mental well-being of all students in high schools.
Keywords: Mental Health; Peer Counselors; Academic Stress; Student Empowerment